PENGARUH SERVICE QUALITY DAN CUSTOMER VALUE TERHADAP LOYALITAS KONSUMEN MELALUI EXPERIENTIAL MARKETING (Studi Pada Bank Sinarmas Kantor Cabang Kota Tanjung Pinang) - Widi Dewi Ruspitasari; Yunus Handoko; Budi Manto (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2022)
One of the companies in the banking sector that participates in the development of the Indonesian economy is Bank Sinarmas where Bank Sinarmas has 2 business units, namely Conventional and Sharia. PT Bank Sinarmas Tbk. Seeing the intense competition in the banking sector, which will result in a wider variety of products and excellent service to support consumer loyalty. With these factors every company must be observant in selling their products and services. In this case, the company can create advantages from their products and services compared to the products and services of other companies. The variables in this study are Service Quality (X1), Customer Value (X2), Experiential Marketing (Z1), and Consumer Loyalty (Y). The population in the study was 6,029 customers, and the research sample was 70 samples using the Slovin formula. The analytical tool used in this research is PLS. The results of the study show that the variables of Service Quality (X1), Customer Value (X2), Experiential Marketing (Z1), and Consumer Loyalty (Y) have a significant effect.Keywords: Service Quality, Customer Value, Experiential Marketing, and Consumer Loyalty.